Policies Implemented in Beijing for Guaranteeing Healthcare for Community-dwelling Patients with Noncommunicable Diseases during the COVID-19 Pandemic - KANG Liangyu, SHANG Weijing, LIU Jue, LIU Min (Zhongguo quanke yixue, 2022)
The COVID-19 pandemic brings about influence and challenge for ensuring healthcare services for non-communicable diseases. To guarantee the healthcare services for community-living patients with non-communicable diseases and to meet their healthcare needs, the Beijing municipal government issued a series of policies and relevant supporting measures, including five parts: promoting the implementation of the extended prescription policy, providing Internet-based medical services, further implementing the hierarchical medical system, giving full play to the role of family doctors, and carrying out the service of doorstep delivery of medicines. We reviewed and summarized policies and corresponding measures implemented in Beijing for guaranteeing healthcare for community-dwelling non-communicable disease patients during COVID-19 early response period and ongoing containment period. By evaluating the implementation effect of the policies and comparing with those at home and abroad, it is found that the community chronic disease management under the continuous epidemic situation can be further optimized in the future from the aspects of strengthening the training of grass-roots medical personnel, paying attention to the monitoring of chronic diseases and their risk factors, accurate health management, continuing to implement the hierarchical diagnosis and treatment system, and exploring the whole cycle health management of chronic diseases.